Leadership and self-evaluation: the best practice for organizational performance today - Mbogori, Zakayo Muriuki; Ongeti, Walter (Research Journal in Advanced Humanities, 2020)
Self-evaluation exercise remains unpopular among many employees and leaders across the globe. This is partly driven by the fact that many people would not want to find out how they are performing as employees or leaders in their respective organizations. This paper presents findings carried out on ten employees at the Ministry of Works in Kenya and their Chief Finance Officer. They were chosen using cluster quota random sampling. The instrument used to collect data was questionnaires and behavior observation while the data analysis techniques were statistic descriptive and multivariate analyses of variance. The study reveals that most employees and leaders who carry out self-evaluation exercises regularly end up being more productive in their organizations and this reflects directly on the performance of their respective organizations. The study recommends that many leaders and followers should carry out self-evaluation exercises to improve their leadership skills and the performance of their organizations.